Komposisi dan Pola Sebaran Makroalga di Perairan Desa Mantang Baru, Kabupaten Bintan, Kepulauan Riau - Pradana, Fendi; Apriadi, Tri; Suryanti, Ani (Biospecies, 2020)
The objective of this study was to determine macroalgae composition, macroalgae distribution, and waters quality in Mantang Baru village, Bintan Regengy, Riau Islands. This research has done on March - May 2019. Sampling points were choosen by purposive sampling method. There were 3 stations based on the ecosystem; coral ecosystem, seagrass ecosystem, and area in front of mangrove ecosystem. Macroalgae were observed by line transect method. Transect was placed at each location for taking macroalgae as many as 3 lines of transect along 100 m, the determination of the first plot was based on the first point of discovery of macroalgae drawn vertical to the coastline between lines 100 m. The results showed that the highest composition in seagrass ecosystem was Chlorophyta (green algae) 59%. Phaeophyta (brown algae) was the higest composition in coral ecoystem and area in front of mangrove ecosystem, with value 69% and 44% respectively. The distribution pattern of macroalgae in Mantang Baru Village waters on each station included a grouping category with a range of values between 1.87 to 3.46. Water quality parametres in Mantang Baru Village met the water quality standard, except nitrate and phosphate.